2020
DOI: 10.1007/s12519-020-00392-y
|View full text |Cite
|
Sign up to set email alerts
|

Why COVID-19 is less frequent and severe in children: a narrative review

Abstract: Background Despite the streaks of severity, severe acute respiratory syndrome-coronavirus-2 (SARS-CoV-2) infection is, in general, less frequent and severe in children than in adults. We searched for causal evidence of this mystery. Data sources An extensive search strategy was designed to identify papers on coronavirus disease 2019 (COVID-19). We searched Ovid MEDLINE, PubMed, EMBASE databases, and Cochrane library and carried out a review on the causes of this dilemma. Results Our searches produced 81 releva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
1
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(65 citation statements)
references
References 99 publications
(131 reference statements)
2
59
1
3
Order By: Relevance
“…Although a decrease in CD4+ T cells was common in adult patients with severe and moderate COVID-19, this finding was rarely seen in children. At birth, there is a greater secretion capacity of IL-10, a cytokine capable of inhibiting inflammatory processes, while in the following years, a greater balance between T helper (Th) 1/Th2/Th17 lymphocytes develops; this finding, described as the immunosenescence phenomenon, helps to explain the different immunological response in adults compared with pediatric patients [ 37 , 38 ].…”
Section: Immunological Response To Infectionmentioning
confidence: 99%
“…Although a decrease in CD4+ T cells was common in adult patients with severe and moderate COVID-19, this finding was rarely seen in children. At birth, there is a greater secretion capacity of IL-10, a cytokine capable of inhibiting inflammatory processes, while in the following years, a greater balance between T helper (Th) 1/Th2/Th17 lymphocytes develops; this finding, described as the immunosenescence phenomenon, helps to explain the different immunological response in adults compared with pediatric patients [ 37 , 38 ].…”
Section: Immunological Response To Infectionmentioning
confidence: 99%
“…Previous studies have demonstrated that some coronaviruses, such as SARS-CoV-2, bind to angiotensin-converting enzyme-2 (ACE2) cell receptors in humans. However, ACE2 expression in the rat lung reduces dramatically with age, a finding seemingly in contrast with the low susceptibility of children to COVID-19 [3] , [14] .…”
Section: Potential Mechanisms Of Children’s Low Susceptibility To Sarmentioning
confidence: 83%
“…To increase the resources, such as hospitals beds and medical staff, procedures deemed elective or non-urgent have been delayed, postponed, or canceled. Based on data regarding the COVID-19 outbreak first in China and then worldwide, children aged less than 10 years old have been found to exhibit significantly lower susceptibility to SARS-CoV-2 infection compared to adults [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
“…Seven of the 36 patients (mean age 5years) were positive for Mycoplasma pneumoniae and another 6/36 were positive for the human metapneumovirus on nasopharyngeal swabs. Studies have further shown children testing negative for SARS-CoV-2 had higher IgG antibody titres against Respiratory syncytial virus (RSV) and/or M. pneumoniae ( 32 ). These findings support the theory that common childhood infections may offer cross protection ( 33 ).…”
Section: Resultsmentioning
confidence: 99%